Criteria for homothetic transformation and rotation for a hole in plane elasticity - Yaghobifar, Mohammad; Nik Long, Nik Mohd Asri (Hikari, 2010)
In this paper, an arbitrary hole in infinite plane elasticity subjected to remote stresses is considered. We investigate the effect of the homothetic transformation and rotation to the considered hole using the governing equations for the displacement. The relation between stresses are obtained.